Matrix methods : an introduction - Bronson, Richard (Academic Press, 1991)
This new edition of Matrix Methods emphasizes applications to Jordan-canonical forms, differential equations, and least squares. The revision now includes an entire new chapter on inner products, additional material on elementary row applications, and hundreds of new exercises.